Quality of life related to health among teaching nurses (Research, Society and Development, 2021)
Objective: This research aimed to assess the health-related quality of life (HRQoL) of nurse professors and preceptors at a University of the State of Mato Grosso. Method: This is a descriptive cross-sectional study, with a quantitative approach. Two instruments were applied, the first of which assessed the socio-demographic, professional and health profile, and the second assessed the quality of life (HRQoL), in August 2020. Results: Of the 27 teachers who heard the prevalence, it was female, 20 (74%), followed by the age group 31 years old 15 (55.6%) and 7 (26.0%) had chronic disease, with arterial hypertension being the most prevalent. When assessing the distribution of quality of life domains, high scores for physical capacity (82.48) were evidenced, followed by mental health (59.85). Teachers have been suffering from social, economic, technological changes in this current pandemic scenario that we are facing, which is giving new directions and meaning to work, causing physical, psychological and behavioral wear, which can negatively affect your health mental. Conclusion: Thus, it concludes the importance and relevance of the theme for the management of nursing work in teaching, further studies are suggested considering the breadth of possibilities that cover this subject, not to mention the intentionality of provoking preparation, reflection, understanding and planning for teachers to have a better quality of life.